Potent in vivo antimalarial activity of water-soluble artemisinin nano-preparations. Issue 59 (1st October 2020) - Valissery, Praveesh; Thapa, Roshni; Singh, Jyoti; Gaur, Deepak; Bhattacharya, Jaydeep; Singh, Agam Prasad; Dhar, Suman Kumar
Abstract : Polymer and liposome-based nanocarriers not only improve the aqueous phase solubility of artemisinin but also helps to retain its therapeutic efficacy in vivo as well. Abstract : Artemisinin is a remarkable compound whose derivatives and combinations with multiple drugs have been utilized at the forefront of malaria treatment. However, the inherent issues of the parent compound such as poor bioavailability, short serum half-life, and high first-pass metabolism partially limit further applications of this drug. In this study, we enhanced the aqueous phase solubility of artemisinin by encapsulating it in two nanocarriers based on the polymer polycaprolactone (ART-PCL) and lipid-based Large Unilamellar Vesicles (ART-LIPO) respectively. Both nanoformulations exhibit in vitro parasite killing activity against Plasmodium falciparum with the ART-LIPO performing at comparable efficacy to the control drug solubilized in ethanol. These water-soluble formulations showed potent in vivo antimalarial activity as well in the mouse model of malaria at equivalent doses of the parent drug. Additionally, the artemisinin-PCL nanoformulation used in combination with either pyrimethamine or chloroquine increased the survival of the Plasmodium berghei infected mice for more than 34 days and effectively cured the mice of the infection. We highlight the potential for polymer and liposome-based nanocarriers in improving not only the aqueous phase solubility of artemisinin but also concomitantly retaining its therapeutic efficacy in vivo as well.